2011
DOI: 10.1002/hbm.21255
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric specialization during mental imagery of brisk walking

Abstract: A new finding in this study is that MI of brisk walking in young healthy individuals strongly involves processes lateralized in right fronto-parietal regions along with left cerebellum. These results show that brisk walking might be a non automatic locomotor activity requiring a high-level supraspinal control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 51 publications
7
31
1
Order By: Relevance
“…These results were confirmed by fMRI studies in which the actual engagement of the participants in the MI task was controlled 59–61 75 Figure 1. summarises the main results of these imaging studies.…”
Section: Motor Imagery Of Locomotion In Cerebral Imaging: From Healthmentioning
confidence: 55%
“…These results were confirmed by fMRI studies in which the actual engagement of the participants in the MI task was controlled 59–61 75 Figure 1. summarises the main results of these imaging studies.…”
Section: Motor Imagery Of Locomotion In Cerebral Imaging: From Healthmentioning
confidence: 55%
“…Within those with PD, we observed significantly lower activity in the left GP than the right, and within controls, we observed higher activity in the left GP with respect to the right, though this difference did not reach significance. One previous investigation also noted increased activity in the left pallidum (but not the right) for healthy adults during imagined walking (Cremers et al, 2012b) however the bilateral changes in PD have not previously been reported. Structural asymmetries in bilateral GP regions may have contributed to these group differences.…”
Section: Discussionmentioning
confidence: 80%
“…We used this approach because we wanted subjects to imagine walking at a self-selected pace. Further, imagining walking faster than preferred can alter BOLD signal (Cremers et al, 2012b; Karachi et al, 2010; Suzuki et al, 2004). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this, right-lateralized frontal lobe functions appear to be associated with operations that should benefit more from perceptually represented content, such as: SWM (20), mental manipulation of objects (21), self-referential mental imagery (22), generating sensory and motoric predictive imagery to help guide ongoing actions (23), holistic integration of plan sequences (14), and integrative/perceptual aspects of category learning (19, 24). …”
Section: The Modelmentioning
confidence: 97%